Influence of Dietary Cation-Anion Differences (DCAD) on Nutrient Intake, Milk Yield and Metabolic Parameters of Transition Buffaloes (Journal of Buffalo Science, 2024)
The study was divided into 2 phases. During 1st phase, 20 pre-partum buffaloes were divided into two groups, given -100 (high negative; HN) and -50 (low negative; LN) mEq/kg of dry matter (DM) diets. In the second phase, +200 (low positive; LP) and +400 (high positive; HP) mEq/kg of DM diets were formulated for postpartum buffaloes. Buffaloes that received LN DCAD were divided into 2 groups (LN-LP and LN-HP), and those that received HN DCAD were also divided into 2 groups (HN-LP and HN-HP). In the first phase, the group fed the HN DCAD diet had significantly lesser DM, nutrient intake, and urine pH (p